Pest and Disease Control Strategies to Increase the Productivity of Shallot Plants (Allium ascalonium L.) - Ach Rovicky*; Widowati Widowati; Astutik Astutik (Universitas Syiah Kuala, 2024)
This study reviews the impact of pest and disease attacks on shallot plants (Allium ascalonium L.) and control strategies to increase plant production. Pests such as Spodoptera exigua (onion caterpillar), Thrips tabaci (thrips), Spodoptera ltura F. (armyworm), Liriomyza spp. (leaf slitting fly), and Gryllotalpa spp. (orong-orong), as well as diseases such as trotol or purple spot (Purple blotch), anthracnose (Antracnose), downy mildew, moler or fusarium wilt (Twisting disease), leaf blight (Stemphylium leaf blight), and leaf spot (Cercospora leaf spot) cause a significant decrease in production hasl. Pest and disease control still relies heavily on chemical pesticides, which pose a risk to the environment and health. Alternative sustainable control such as the use of biopesticides from mahogany seed extract (Swietenia mahagoni), Japanese papaya leaf extract (Cnidoscolus aconitifolius), and legundi weed extract (Vitex trifolia L.), as well as the application of Plant Growth Promoting Microorganisms (PGPM) from bamboo root can have a very good influence on controlling pests and diseases of shallot plants and can help in increasing plant productivity